KEDUDUKAN ANAK PEREMPUAN BATAK DI JAKARTA DITINJAU DARI HUKUM WARIS ADAT (STUDI PUTUSAN NOMOR 151/PDT.G/2020/PN.PST): The Position of Batak Female Children in Jakarta Reviewed from Traditional Inheritance Law (Study Decision Number 151/Pdt.G/2020/Pn.Pst) - Nabilah Arwi; Ning Adiasih (AMICUS CURIAE, 2025)
The patrilineal system is upheld by the Batak community, which results in differing responsibilities for male and female children. As a consequence, women do not inherit property. The identification problem of this study addresses how inheritance rights for female children in the Batak community residing in Jakarta have evolved, as established by Decision Number 151/Pdt.G/2020/PN Jkt.Pst following the issuance of Jurisprudence No. 3/Yur/Pdt/2018. Additionally, it looks at the reasoning behind the judge's ruling in Case Number 151/Pdt.G/2020/PN Jkt.Pst. The study uses a descriptive methodology and normative legal research techniques, utilizing secondary data analyzed qualitatively and concluded deductively. The result and conclusion in Decision Number 151/Pdt.G/2020/PN Jkt.Pst, the inheritance rights of female children in the Batak community in Jakarta are recognized as equal to those of male children. The judge's consideration in this ruling is that female children are entitled to inheritance, which deviates from the traditional Batak customs still observed in their native regions, where inheritance such as land typically passes to male children, excluding females.